Komunikasi Dan Penyiaran Islam dalam Perjalanan Haji dan Umrah - Ridwan, Aang; Ramlan, Ariq; Fauzidan, Fauzidan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
Islamic communication and broadcasting in the practice of pilgrimage and umrah is an important theme that is rarely highlighted, although in a separate focus of discussion, each theme has been widely studied. A good and effective Islamic communication and broadcasting practices are needed to support the services and guidance of Hajj and Umrah pilgrims. This is based on the objective conditions of the Hajj and Umrah journeys, especially related to religious guidance that has not been able to meet the needs and expectations of the pilgrims themselves. This study is basically an attempt by researchers to investigate how the themes of Islamic communication and broadcasting studies in the pilgrimage and umrah trips are discussed and reviewed in various existing scientific publications. Therefore, the chosen form of research is literature review, which focuses on publishing articles in various Scopus indexed journals and the Google Scholar article database on related themes in the 2010-2021 period. The results showed: (1) Conceptual attributes: Islamic communication and broadcasting is understood as a field of study that examines communication practices for the development of Islamic da'wah in harmony with Islamic principles and teachings; (2) Antecedents: the lack of studies, the actual condition of the management of the Hajj and Umrah pilgrimages, as well as the need for changes in service orientation and communication in the Hajj and Umrah journeys; (3) Consequences: increasing the faith and religiosity of the congregation, the delivery of Islamic messages to the congregation, increasing the understanding of the congregation, and increasing awareness to present competent Hajj and Umrah travel guides; (4) Socio-cultural context: changes in the socio-cultural, political, economic situation and patterns of community religiosity; and (5) Related concepts: adding other scientific perspectives to the study of Islamic communication and broadcasting in the pilgrimage and umrah journeys.